(untitled) (MSW Management Journal, 2025)
The management of Municipal Solid Waste (MSW) represents a complex activity that makes reference to innovative solutions and inclusiveness, considering the new realities of waste. The bibliometric analysis provides a powerful navigation tool for going through the vast literature that is accumulating on MSW and public perception through knowledge integration into research and practice, making it helpful to foster collaboration, stimulate innovation, and strengthen communities in moving toward adopting sustainable behaviours which support greater environmental sustainability as well as healthier, resilient societies. This paper uses bibliometrics to analyse the global literature based on MSW management to identify common practices, significant countries, notable organisations and thematic foci that characterise the discipline and which would enable a holistic appreciation of this subject matter. It contributes to the newly emerging body of discussions towards sustainable waste management in so far as this research takes extensive bibliometric regarding MSW and Public Perceived by Knowledge Integration into research and practice.